Airway management in the emergency department. Issue 1 (1st January 2002) - Clancy, M; Nolan, J
Abstract : Airway management in the emergency department and the role of anaesthetists and emergency physicians is reviewed. The training for emergency physicians in the advanced airway skills of rapid sequence induction and tracheal intubation is discussed.